Microbial community niches on microplastics and prioritized environmental factors under various urban riverine conditions - 히엔 티 뉴옌; 최우단; 김은주; 조경진 (Elsevier BV, 2022)
Microplastics (MPs) provide habitats to microorganisms in aquatic environments; distinct microbial niches have re-cently been elucidated. However, there is little known about the microbial communities on MPs under urban riverine conditions, in which environmental factors fluctuate. Therefore, this study investigated MP biofilm communities under various urban riverine conditions (i.e., organic content, salinity, and dissolved oxygen (DO) concentration) and evaluated the prioritized factors affecting plastisphere communities. Nine biofilm-forming reactors were operated under various environmental conditions. Under all testing conditions, biofilms grew on MPs with decreasing bacterial diversity. Interestingly, biofilm morphology and bacterial populations were driven by the environmental parameters. We found that plastisphere community structures were grouped according to the environmental conditions; organic content in the water was the most significant factor determining MP biofilm communities, followed by salinity and DO concentration. The principal plastisphere communities were Proteobacteria, Bacteroidetes, Cyanobacteria, and Firmicutes phyla. In-depth analyses of plastisphere communities revealed that biofilm-forming and plastic-degrading bacteria were the predominant microbes. In addition, potential pathogens were majorly discovered in the riverine wa-ters with high organic content. Our results suggest that distinct plastisphere communities coexist with MP particles under certain riverine water conditions, implying that the varied MP biofilm communities may affect urban riverine ecology in a variety of ways.